Tourism and Recreation Preferences in River Environments: : Evaluating Gen Z’s Motivations and Activity Choices - Arsyul Salam, Dicky; Rahmanda Putra, Rifki (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
This study investigates the preference and motviations of Generation Z tourist in river enviromnets, with focul on West Java, Indonesia. Using a structured survey approach targeting 140 respondents, the research findings indicate that recreational motivations and connection with nature are central to visitor satisfaction, complemented by infrastructure quality and tranquility. Statistical analysis revealed strong interconnections between the factors influencing activity choices and the quality of visitor experiences, providing deeper insight into what drives satisfaction in river environments.. The study underscores the potential of river-based tourism to integrate environmental, cultural, and economic objectives while addressing sustainability challenges. Future research should explore longitudinal studies and expanded cultural contexts to further optimize tourism strategies.